A Brief Look at Current Usda Work on Pests and Diseases. (1st August 2021) - Unknown
If a farmer has nematode problems or has too many weeds or fungal attacks a simple solution is to spread some mustard on them. Agricultural Research Service and university scientists are experimenting with mustards as an alternative to fighting crop pests chemically. The system biofumigates pests with stands of white mustard, brown mustard, and rapeseed.. Biofumigation refers to natural substances plants release while decomposing that make surrounding soils toxic to some weeds, nematodes, and fungi. The experiments, in Washington State, dovetail with increasing grower interest in mustard crops for pest control and as "green manure" meaning it can be disked into soil to improve tilth, organic matter, aeration, and water filtration. Despite such benefits, there is still much to learn about how mustards control pests and under what conditions they work best.